(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Medicine is not only a science, but also a historically defined system of public institutions. They say that nursing is the youngest science and the oldest art. As a science, nursing has its own history that spans many millennia. The origin of medicine is associated with the stages of human development and human society. According to many experts, the first medical institutions arose in human society not in connection with beliefs, but in connection with living conditions, nutrition, and the struggle for continued existence.